Satisfaction with a 2-day communication skills course culturally tailored for medical specialists in Qatar - Carma L Bylund; Khalid Alyafei; Abdelhamid Afana; Sheyma Al-Romaihi; Mohammed Yassin; Maha Elnashar; Banan Al-Arab; Abdullatif Al-Khal (Journal of Family and Community Medicine, 2017)
OBJECTIVE: Health-care communication skills training may be particularly needed in the Arabian Gulf countries because of the variety of cultures within the physician and patient populations. This study describes the implementation and results of a communication skills training program for physicians in Qatar that assessed previous training, and effect of previous training on participants' course evaluations. MATERIALS AND METHODS: We conducted a 2-day communication skills training course covering seven culturally adapted modules. Educational strategies included large and small group work with the standardized patient, demonstration videos, and lectures. At the end, participants completed a course evaluation survey. Data analysis performed with SPSS; frequencies and percentages were calculated, and Chi-square test applied to evaluate statistical significance. RESULTS: A total of 410 physicians in Qatar have participated in the course over a period of 2 years. Evaluation ratings of the course were high. Participants rated the module on Breaking Bad News as the most useful, and the small group role-play as the most helpful course component. One-third of participants had previously participated in experiential communication skills training. There was no association between previous experience and evaluation of the course. CONCLUSION: Physicians in Qatar positively evaluated a 2-day communication skills course, though the majority of participants did not have any previous exposure to experiential communication skills training.